Distribution of HLA alleles in the semang and senoi orang asli populations in Peninsular Malaysia - Abd Razak, Tasnim (2015)
Several waves of human migration into Peninsular Malaysia led to the stratification of various ethnic groups. The earliest inhabitants of Peninsular Malaysia are the Orang Asli population, namely Semang, Senoi and Proto Malay. In the present study, we typed the HLA-A, -B and -DRB1 loci of the two oldest Orang Asli populations, Semang and Senoi. Sequence-based HLA typing was performed on 85 individuals from four Orang Asli subgroups: Kensiu (N = 21) and Bateq (N = 16) of the Semang major group, and Che Wong (N = 10) and Semai (N = 38) of the Senoi major group. A total of 11, 21 and 17 HLA-A, -B and -DRB1 alleles were identified, respectively in the studied Orang Asli subgroups. HLA-A*02:01 was the most common allele in Kensiu, Bateq and Che Wong, and A*24:07 was the most common in Semai. B*18:01 was the most common allele in all of the Orang Asli subgroups. DRB1*09:01 was the most common allele in Kensiu and Che Wong, and DRBI*12:02 was the most common allele in Bateq and Semai. The following twoloci haplotypes were common in the Orang Asli subgroups: HLA-A*02:01-B*18:01, A*02:01-DRB1*09:01, A*02:01-DRB1*12:02, B*15:13-DRB1*12:02 and B*18:01- DRB1*09:01. The three-loci, HLA-A*02:01-B*18:01-DRB1*09:01 haplotype was observed in all the Orang Asli subgroups. The HLA analysis in this study suggested that the Orang Asli subgroups experienced genetic drift based on evidence of limited allelic diversity. Correspondence analysis based on HLA-A, -B and -DRB1 allele frequencies suggested that the Orang Asli subgroups share high genetic affinity with the populations from South China, Indochina, Malaysia, Singapore and Indonesia. Although the HLA data is not conclusive to correlate the Semang with the African population, there was one individual who expressed DRB1*15:03 allele in the Kensiu where this allele is observed in high frequency in Africa. The Semang HLA allelic characteristics showed similar profiles with those of other Southeast Asian populations probably due to evolutionary pressure on the HLA gene complex. The HLA data also demonstrated similar HLA allelic profiles of the Senoi with Indochina/South China populations. In conclusion, HLA allelic profiles of the Orang Asli subgroups can be said to be characteristically Southeast Asian. The establishment of HLA database for selected Orang Asli subgroups may provide useful reference in clinical applications (e.g. cell and organ transplants), HLAdisease association studies, HLA-adverse drug reaction association studies and DNA marker for personal identification and population genetics.